The CELF Family of RNA Binding Proteins Is Implicated in Cell-Specific and Developmentally Regulated Alternative Splicing - Ladd, Andrea N. (American Society for Microbiology, 2001)
Alternative splicing of cardiac troponin T (cTNT) exon 5 undergoes a developmentally regulated switch such that exon inclusion predominates in embryonic, but not adult, striated muscle. We previously described four muscle-specific splicing enhancers (MSEs) within introns flanking exon 5 in chicken cTNT that are both necessary and sufficient for exon inclusion in embryonic muscle. We also demonstrated that CUG-binding protein (CUG-BP) binds a conserved CUG motif within a human cTNT MSE and positively regulates MSE-dependent exon inclusion. Here we report that CUG-BP is one of a novel family of developmentally regulated RNA binding proteins that includes embryonically lethal abnormal vision-type RNA binding protein 3 (ETR-3). This family, which we call CELF proteins for CUG-BP- and ETR-3-like factors, specifically bound MSE-containing RNAs in vitro and activated MSE-dependent exon inclusion of cTNT minigenes in vivo. The expression of two CELF proteins is highly restricted to brain. CUG-BP, ETR-3, and CELF4 are more broadly expressed, and expression is developmentally regulated in striated muscle and brain. Changes in the level of expression and isoforms of ETR-3 in two different developmental systems correlated with regulated changes in cTNT splicing. A switch from cTNT exon skipping to inclusion tightly correlated with induction of ETR-3 protein expression during differentiation of C2C12 myoblasts. During heart development, the switch in cTNT splicing correlated with a transition in ETR-3 protein isoforms. We propose that ETR-3 is a major regulator of cTNT alternative splicing and that the CELF family plays an important regulatory role in cell-specific alternative splicing during normal development and disease.